Islamic Banking: Role of Customer’s Perception and Awareness to make it ‎competitive with Conventional Banking - KAZMI, ESMAT; JAMIL, MUHAMMAD (International Journal of Islamic Economics and Governance, 2022)
The present study aims to highlight the issues related to the growth of Islamic ‎Banking. Because of various modes of Islamic banking, the banking system is ‎growing not only in Muslim countries but also in non-muslim countries. Likewise, ‎Islamic banking is also growing in Pakistan in terms of its market capitalization as ‎well as its banking accounts. However, despite the dominance of Muslims in the ‎Islamic Republic of Pakistan, the growth of Islamic banking is not up to ‎expectations. The present study aims to highlight the issues that create hurdles in ‎the growth of Islamic banking. Based on the survey from the users and non-users ‎of banking, the study postulates the reasons for the slow growth of Islamic ‎banking. This study analyzes the customers’ perception and awareness level ‎towards the IBI. It further investigates the relationship between different ‎demographic variables and the perception and awareness of customers. A sample of ‎‎267 respondents from different regions of Muzaffarabad was selected. For the ‎analysis, descriptive statistics & Logistic regression was adopted to check the ‎relationship between demographic variables and perception and awareness. The ‎respondents expressed their perception of some of the services and expressed ‎dissatisfaction with few. Customers indicate that they are aware of different ‎products but do not adopt these products‎.